Effects of human-induced load models on tuned mass damper in reducing floor vibration. Issue 11 (August 2019) - Chen, Jun; Han, Ziping; Xu, Ruotian
Dozens of human-induced load models for individual walking and jumping have been proposed in the past decades by researchers and are recommended in various design guidelines. These models differ from each other in terms of function orders, coefficients, and phase angles. When designing structures subjected to human-induced loads, in many cases, a load model is subjectively selected by the design engineer. The effects of different models on prediction of structural responses and efficiency of vibration control devices such as a tuned mass damper, however, are not clear. This article investigates the influence of human-induced load models on performance of tuned mass damper in reducing floor vibrations. Extensive numerical simulations were conducted on a single-degree-of-freedom system with one tuned mass damper, whose dynamic responses to six walking and four jumping load models were calculated and compared. The results show a maximum three times difference in the acceleration responses among all load models. Acceleration response spectra of the single-degree-of-freedom system with and without a tuned mass damper were also computed and the response reduction coefficients were determined accordingly. Comparison shows that the reduction coefficient curves have nearly the same tendency for different load models and a tuned mass damper with 5% mass ratio is able to achieve 50%–75% response reduction when the structure's natural frequency is in multiples of the walking or jumping frequency. All the results indicate that a proper load model is crucial for structural response calculation and consequently the design of tuned mass damper device.